Brand psychology : The art and science of building strong brands - Busche, Laura (New York : Routledge, 2024)
"Brand Psychology brings together theory and practice from the fields of psychology, design, and marketing to demystify the brand development process. It explores the behavioral science behind brand building, looking at the psychological principles at play whenever a brand is built and communicated"
Keywords: Branding (Marketing) -- Psychological aspects; Product management -- Psychological aspects; Product management-Psychological aspects